2002
DOI: 10.1093/jnci/94.11.852
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Performance of HER2 Testing--National Surgical Adjuvant Breast and Bowel Project Experience

Abstract: Trastuzumab (Herceptin) provides clinical benefits for patients diagnosed with advanced breast cancers that have overexpressed the HER2 protein or have amplified the HER2 gene. The National Surgical Adjuvant Breast and Bowel Project (NSABP) Protocol B-31 is designed to test the advantage of adding Herceptin to the adjuvant chemotherapeutic regimen of doxorubicin and cyclophosphamide followed by paclitaxel (Taxol) in the treatment of stage II breast cancer with HER2 overexpression or gene amplification. Eligibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

10
242
0
10

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 435 publications
(262 citation statements)
references
References 12 publications
10
242
0
10
Order By: Relevance
“…Reliable, high-quality HER2 testing for clinical use is of paramount importance for the correct identification of patients who would benefit from HER2-targeted therapies. 1,[14][15][16][17][18] False-negative HER2 assessments could result in denial of an effective treatment, while false-positive assessments may lead to inappropriate administration of a potentially harmful, costly, and ineffective HER2-targeted therapy, or exclusion from treatment with other targeted therapies in the HER2-negative setting. 1,8,11,19,20 Despite 410 years of routine HER2 testing, studies have demonstrated variability in HER2 positivity assessments between local pathology laboratories and central testing centers, posing a challenge for clinicians.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Reliable, high-quality HER2 testing for clinical use is of paramount importance for the correct identification of patients who would benefit from HER2-targeted therapies. 1,[14][15][16][17][18] False-negative HER2 assessments could result in denial of an effective treatment, while false-positive assessments may lead to inappropriate administration of a potentially harmful, costly, and ineffective HER2-targeted therapy, or exclusion from treatment with other targeted therapies in the HER2-negative setting. 1,8,11,19,20 Despite 410 years of routine HER2 testing, studies have demonstrated variability in HER2 positivity assessments between local pathology laboratories and central testing centers, posing a challenge for clinicians.…”
mentioning
confidence: 99%
“…1,8,11,19,20 Despite 410 years of routine HER2 testing, studies have demonstrated variability in HER2 positivity assessments between local pathology laboratories and central testing centers, posing a challenge for clinicians. 15,[21][22][23][24][25] In some of these studies it was assumed that variations in HER2 positivity at individual centers equated to problems with testing quality. 15,22,26,27 To overcome this issue, monitoring of HER2 positivity rates has been suggested as a means for HER2 testing quality control in international guidelines.…”
mentioning
confidence: 99%
“…[8][9][10][11] SISH was implemented more recently and three studies reported a 97, 96 and 87% concordance between SISH and FISH results on excision samples [12][13][14] taking into account that discordant cases could be partly explained by intratumor heterogeneity of amplification. One study showed an 89% concordance of SISH results between surgical specimens and core-needle biopsies but the number of studied cases was limited (n ¼ 56).…”
mentioning
confidence: 99%
“…Specimen availability may be related to tumour size and patient outcome (Hoppin et al, 2002), and the quantity, quality, and preservation method of the specimen may affect feasibility of conducting certain assays. There can also be biases or large variability inherent in the assay results, depending on the particular assay methods used (Thor et al, 1999;Gancberg et al, 2000; McShane et al, 2000;Paik et al, 2002;Roche et al, 2002). Statistical problems are commonplace.…”
mentioning
confidence: 99%